Hear.say = 听。说 － 失声子. - Ng, Yi Han. (2011)
This report aims to chronicle my journey of producing a radio drama for my Final Year Project (FYP). It begins with an introduction of my motivation, followed by some background about radio dramas around the world. After setting up the project proposal and objectives, it also records the various obstacles I had to overcome during the three stages of production. The report concludes with a focus group evaluation as well as my own reflections on this project.